Refleksi Metafisis Atas Pancasila - Made Pramono, (Pelangi Ilmu, 2007)
Abstract Pancasila is Indonesians Philosophy. As philosophical concept, Pancasila has three dimensions: ontology, epistemology, and axiology. This article will not discuss all of this, but to reflect in a metaphysical base which focus in ontologycal status of Pancasila. This metaphysical reflection will use Phenomenology-Existensialism and Critical Theory in regard to objectivy the subjectivity of reflection.